Design of One-dimensional Photonic Crystals Using Combination of Band Diagram and Photonic Gap Map Approaches - PEROVA, TANIA (American Institute of Physics, 2008)
The design of one-dimensional photonic crystals and the analysis of their optical properties have been performed using band diagram and forbidden gap map methods. It has been shown that the latter method is more useful for practical applications since (i) it can be applied for any number of periods and (ii) it is more suitable for the selection of a filling fraction in a wide range of values using a single graphical presentation. Three different types of photonic crystals with small, medium, and high optical contrast were modeled using both methods. The features of the omnidirectional band gap formation for photonic crystals with small optical contrast and low number of periods have been explained. The formation of a one-dimensional photonic structure with limited number of periods and omnidirectional band gap close to that for an infinite periodic structure has been discussed.
PUBLISHED
Keywords: Photonic crystals